International orders in the early modern world before the rise of the West - Suzuki, Shogo 1975-; Zhang, Yongjin; Quirk, Joel (New international relations, 2014)
This book examines the historical interactions of the West and non-Western world, and investigates whether or not the exclusive adoption of Western-oriented 'international norms' is the prerequisite for the construction of international order